The Effect of Profitability and Leverage on Firm Value (Basic industry and chemical sub-sector cement listed on the Indonesia Stock Exchange in 2016-2019) - Dick Wolters Marbun; Harman Malau (Ekonomis: Journal of Economics and Business, 2021)
This study aims to determine the effect of profitability and leverage on the value of companies in the basic industry sector and cement sub-sector chemicals listed on the Indonesia Stock Exchange in 2016-2019. The sample in this study is the basic industrial sector companies and the cement sub-sector chemical listed on the Indonesia Stock Exchange. The sampling method used in this study is saturated sampling with a sample of 6 companies in the basic industrial sector and cement sub-sector listed on the Indonesia Stock Exchange for the last 4 years. This study uses descriptive statistical methods, correlation coefficient analysis, coefficient of determination analysis, simple linear regression, and significance test (t test). This study uses data from the annual financial statements of companies in the basic and chemical sub-sector of cement and components listed on the Indonesia Stock Exchange in 2016-2019. Secondary data is processed using SPSS. The results showed that profitability and leverage had no effect on firm value.